A new floating sensor array to detect electric near fields of beating heart preparations - Hofer, E.; Keplinger, F.; Thurner, T.; Wiener, T.; Sanchez-Quintana, D.; Climent, V.; Plank, G. (Biosensors & bioelectronics, 2006)
A new flexible sensor for in vitro experiments was developed to measure the surface potential, Φ, and its gradient, E (electric near field), at given sites of the heart. During depolarisation, E describes a vector loop from which direction and magnitude of local conduction velocity θ can be computed. Four recording silver electrodes (14 μm × 14 μm) separated by 50 μm, conducting leads, and solderable pads were patterned on a 50 μm thick polyimide film. The conductive structures, except the electrodes, were isolated with polyimide, and electrodes were chlorided. Spacer pillars mounted on the tip fulfil two functions: they keep the electrodes 70 μm from the tissue allowing non-contact recording of Φ and prevent lateral slipping. The low mass (9.1 mg) and flexibility (6.33 N/m) of the sensor let it easily follow the movement of the beating heart without notable displacement. We examined the electrodes on criteria like rms-noise of Φ, signal-to-noise ratio of Φ and E, maximum peak-slope recording d Φ/d t, and deviation of local activation time (LAT) from a common signal and obtained values of 24–28 μV, 46 and 41 dB, 497–561 V/s and no differences, respectively. With appropriate data acquisition (sampling rate 100 kHz, 24-bit), we were able to record Φ and to monitor E and θ on-line from beat-to-beat even at heart rates of 600 beats/min. Moreover, this technique can discriminate between uncoupled cardiac activations (as occur in fibrotic tissue) separated by less than 1 mm and 1 ms.